2015
DOI: 10.1111/bjd.13747
|View full text |Cite
|
Sign up to set email alerts
|

4-Hexyl-1,3-phenylenediol, a nuclear factor-κB inhibitor, improves photodamaged skin and clinical signs of ageing in a double-blinded, randomized controlled trial

Abstract: Inhibition of the proinflammatory NF-κB pathway resulted in increased expression of ECM proteins in vitro and significant clinical improvement in photodamaged skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…NF-κB inhibition can enhance the expression of extracellular matrix (ECM) genes in vitro. In one small eight week randomized clinical trial (RTC), the inhibition of NF-κB was shown to decrease the visible signs of aging [25]. This further corroborates the role of NF-κB in skin aging.…”
Section: Introductionmentioning
confidence: 56%
“…NF-κB inhibition can enhance the expression of extracellular matrix (ECM) genes in vitro. In one small eight week randomized clinical trial (RTC), the inhibition of NF-κB was shown to decrease the visible signs of aging [25]. This further corroborates the role of NF-κB in skin aging.…”
Section: Introductionmentioning
confidence: 56%
“…Hence, the blackberrydill combination identified here could potentially be used for wrinkle-reducing treatment to provide anti-ageing skin benefits. Although other studies have shown elastogenesis stimulation through single ingredients [11,18,[43][44][45], this is the first study to use a comprehensive approach to upregulate elastogenesis stimulation in adults by combining two extracts that increase skin's functional elastic fibre production as well as prevent their degradation. Taken together, our studies identified a combination of two complementary natural extracts with elastogenic, skinfirming and sagging-reducing benefits for ageing and photodamaged skin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to UV exposure, other factors can also impact elastin in skin. Induction of the inflammatory mediator, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-jB), has been shown to repress elastin and collagen gene expression and to contribute to the clinical appearance of photodamaged skin [11]. Taken together, elastin expression and organization can be negatively affected in skin resulting in the loss of elasticity seen in ageing and photodamaged skin.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that this is indeed the case has been presented in a clinical study that tested the effect of topically administered 4-hexyl-1,3-phenylenediol, an NF-kB inhibitor on photo-damaged skin. After eight weeks of use, patients being treated with the NF-kB inhibitor showed significant improvement in crow's feet fine lines, cheek wrinkles, age spots, mottled pigmentation and radiance [218]. A role for NF-kB in contributing to chronological aging has been demonstrated in studies with fibroblasts obtained from donors over the age of 50.…”
mentioning
confidence: 99%
“…These cells showed increased basal NF-kB activity, consistent with a slow increase in inflammation that occurs in aging skin. Treatment of these fibroblasts with 4-hexyl-1,3-phenylenediol, increased the expression of extracellular matrix (ECM) genes [218].…”
mentioning
confidence: 99%